2010
DOI: 10.1038/ajg.2009.699
|View full text |Cite
|
Sign up to set email alerts
|

CIMP Status of Interval Colon Cancers: Another Piece to the Puzzle

Abstract: Interval cancers are more likely to arise in the proximal colon and demonstrate CIMP, which suggests there may be differences in biology between these and non-interval CRC. Additional studies are needed to determine whether interval cancers arise as a result of missed lesions or accelerated neoplastic progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
257
1
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 345 publications
(267 citation statements)
references
References 26 publications
6
257
1
3
Order By: Relevance
“…In a non-populationbased screening setting in North America, interval cancers have been associated with proximal location and molecular traits, such as CpG island methylation phenotype (CIMP) [60], that occur in most sessile serrated lesions and traditional serrated adenomas [25]. Under-detection of non-polypoid and serrated lesions may therefore play a role in study results that have not shown a protective effect of colonoscopy against CRC mortality in the right colon [61,62].…”
Section: Author Manuscriptmentioning
confidence: 93%
“…In a non-populationbased screening setting in North America, interval cancers have been associated with proximal location and molecular traits, such as CpG island methylation phenotype (CIMP) [60], that occur in most sessile serrated lesions and traditional serrated adenomas [25]. Under-detection of non-polypoid and serrated lesions may therefore play a role in study results that have not shown a protective effect of colonoscopy against CRC mortality in the right colon [61,62].…”
Section: Author Manuscriptmentioning
confidence: 93%
“…In the literature, mixed results have been published regarding the prognostic role of CIMP in CRC. 16,[29][30][31] To the best of our knowledge, there currently are no set guidelines for labeling CRC as CIMP-high because incidences vary depending on the panel of genes selected, choices of probes, location of the methylation island, cutoff points, and the technology used. Therefore, a consensus must be established for true comparison among different population.…”
Section: Survival Analysismentioning
confidence: 99%
“…These features likely account for the fact that the serrated pathway is a disproportionate contributor to interval CRC (CRC diagnosed relatively soon after colonoscopy). Cancers associated with the serrated pathway tend to occur in the proximal colon and their molecular signature overlaps significantly with interval CRC [21][22][23] .…”
mentioning
confidence: 99%